Determinants of customer’s loyalty: An empirical study of Malaysian retail banking industry - Tan, William Wey Lian (2023)
The primary goal of this research is to determine the factors that influence customer loyalty in the domestic retail banking industry. Specifically, the study examines the effects of service quality, customer knowledge management, and confirmation on customer satisfaction, as well as the impact of corporate reputation on customer trust. The study also aims to investigate how customer satisfaction and trust influence customer loyalty in the domestic retail banking sector. The research instrument used for this study was self-administered questionnaires, and 356 questionnaires were distributed to customers in the Klang Valley through social messaging platforms over a period of three weeks. The findings of the study suggest that service quality, customer knowledge management, and confirmation are significantly related to customer satisfaction in the domestic retail banking sector. Additionally, corporate reputation is positively related to customer trust in the industry. Finally, the study confirms that customer satisfaction and trust have a positive impact on customer loyalty. In summary, the research presents an enhanced comprehension of the variables impacting customer loyalty within the Malaysian retail banking sector, offering valuable insights for academician’s better understanding as well as allows industry stakeholders to improve and sharpen their competitive edge in the market.